Analysis of Speech and Thought Presentation in Children’s Storybook Frozen: A Stylistic Study - Putu Mayra Elke Shafira,; Ni Made Diana Erfiani,; Yohanes Octovianus L. Awololon, (RETORIKA: Jurnal Ilmu Bahasa, 2024)
Stylistic speech and thought presentation play crucial roles in shaping characters and enriching readers' experiences in children’s storybooks. This study delved into the depiction of speech and thought in the "Frozen" Storybook, an adaptation of Disney's 2013 film. Employing a non-participant descriptive qualitative methodology, the research analyzes internet-accessible data, employing the framework proposed by Leech and Short (2007), categorizing speech and thought into ten distinct categories. The analysis uncovers eight presentation types across twenty-two instances, with speech representation occurring twelve times and thought representation ten times. Predominant categories include IS (Indirect Speech), FIT (Free Indirect Thought), and NRTA (Narrative Report of Thought and Action), each appearing four times. Additionally, FDS (Free Direct Speech), DS (Direct Speech), FIS (Free Indirect Speech), and IT (Indirect Thought) occur three or two times, while NRSA (Narrative Report of Speech Act) occurs once. Notably, DT (Direct Thought) and FDT (Free Direct Thought) are absent. Analyzing speech and thought presentation in children’s storybooks yields insights into characters' communication and cognition, aiding readers, particularly children, in understanding motivations, emotions, and personalities. Furthermore, it fosters language development and enhances comprehension skills by exposing young readers to diverse presentation forms. Additionally, it contributes to literary analysis by elucidating authors' stylistic choices and their storytelling impacts. Ultimately, examining speech and thought presentation enhances both reading experiences and scholarly discourse on children’s literature.